Maitripa : India's yogi of nondual bliss - Mathes, K. (Boulder, Colorado : Shambhala, 2021)
Buddhist traditions are heir to some of the most creative thinkers in world history. The Lives of the Masters series offers lively and reliable introductions to the lives, works, and legacies of key Buddhist teachers, philosophers, contemplatives, and writers. Each volume in the Lives series tells the story of an innovator who embodied the ideals of Buddhism, crafted a dynamic living tradition during his or her lifetime, and bequeathed a vibrant legacy of knowledge and practice to future generations.
Includes references and index.